Agon, los a może fatum? Milana Kundery zmagania z Europą Środkową - Brodacka, Magdalena (Bohemistyka, 2021)
The aim of the paper is to reconstruct the Central European idea in Milan Kundera’s work. The study analyses key works for the Central European category: The Book of Laughter and Forgetting and The Stolen West or The Tragedy of Central Europe. This text is an attempt to create the Kundera’s dictionary of Central Europe, and therefore it addresses such categories as fate and fate, memory and forgetfulness, scapegoat theory and the metaphorical death of the novel. The article highlights the key role of culture as a matter of Central European identity in opposition to the dominant historical-political discourse.